Operationalizing al-Shawkânî’s Ecological Values: A Tripartite Framework for Islamic Ecopedagogy - Syaeful Rokim; Shalih Ali Al-Shahri; Budi Setiawan (Ulul Albab: Jurnal Studi Islam, 2026)
The escalating global environmental crisis calls for innovative pedagogical frameworks capable of fostering ecological consciousness across diverse cultural and religious contexts. However, a persistent gap remains between the ecological values embedded in classical Quranic exegesis and their practical application in contemporary educational settings. This study addresses this gap by developing an Islamic ecopedagogical framework based on al-Shawkânî’s interpretation of Q.S. al-A‘râf (7:56–58) and aligning it with UNESCO’s Education for Sustainable Development (ESD 2030) agenda. Employing a qualitative-hermeneutical approach, the study analyzes al-Shawkânî’s tafsir alongside contemporary ecopedagogy literature to explore the educational implications of Quranic ecological ethics. The findings reveal four core ecological values: (1) anti-exploitative ethics (fasâd); (2) spiritual interconnectedness between humans and nature; (3) ecological sustainability and regeneration; and (4) gratitude-based environmental ethics. These values are systematically operationalized into a tripartite pedagogical framework consisting of spiritual internalization, curriculum transformation, and eco-project-based learning. Theoretically, this study contributes to Islamic education and sustainability scholarship by demonstrating how ecological values derived from classical Quranic exegesis can be translated into a structured ecopedagogical framework. Practically, it offers a scalable model that aligns Islamic educational traditions with the objectives of ESD 2030 and provides a contextually grounded approach for strengthening environmental stewardship and localizing global sustainability agendas within madrasahs and pesantren.